Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1029/2007eo080002
|View full text |Cite
|
Sign up to set email alerts
|

Storm impacts on potential pathogens in estuaries

Abstract: Estuarine and coastal environments are susceptible to a variety of changes driven by tropical storms and hurricanes. The 2005 Atlantic hurricane season impressed upon the public the devastating impacts of storms on coastal populations and the possible social and public health costs. Storm surges and subsequent flooding have the potential to redistribute water and associated contaminants, including a wide range of chemicals and microorganisms. While this impact is difficult to observe through monitoring during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…Smaller containers of surface and bottom waters were collected during each sampling event for turbidity measurement, which was done using a Hach 2100P turbidimeter (turbidity was not measured for the July and August sampling events). This was used to represent the total suspended solids (Fries et al 2007). Water samples were transported in coolers with frozen gel packs to the microbiology lab at the National Oceanic and Atmospheric Administration’s Center for Coastal Environmental Health and Biomolecular Research (CCEHBR) in Charleston, S.C. and analyzed within 6–8 h of collection.…”
Section: Methodsmentioning
confidence: 99%
“…Smaller containers of surface and bottom waters were collected during each sampling event for turbidity measurement, which was done using a Hach 2100P turbidimeter (turbidity was not measured for the July and August sampling events). This was used to represent the total suspended solids (Fries et al 2007). Water samples were transported in coolers with frozen gel packs to the microbiology lab at the National Oceanic and Atmospheric Administration’s Center for Coastal Environmental Health and Biomolecular Research (CCEHBR) in Charleston, S.C. and analyzed within 6–8 h of collection.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that cholera outbreaks occur seasonally and correlate with the monsoon in areas where cholera is endemic (11,20,46). Furthermore, seasonal fluctuations in rainfall as well as changes in sea surface height brought by tides and storm surges can cause wide variations in salinity concentrations, which affect the growth and distribution of the pathogen (15,20,57). Salinity is therefore a significant driving force in the occurrence of V. cholerae and cholera outbreaks.…”
mentioning
confidence: 99%
“…V. cholerae inhabits aquatic environments, and its occurrence strongly correlates with salinity (15,24,33,37). Interannual climate variation is thought to have a significant impact on the environmental conditions governing V. cholerae occurrence and the incidence of cholera outbreaks (29,47,52).…”
mentioning
confidence: 99%